1996
DOI: 10.2135/cropsci1996.0011183x003600060042x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA Marker Technologies in Characterizing Plant Genome Diversity: Variability in Chinese Sorghums

Abstract: Chinese sorghums [Sorghum bicolor (L.) Moench] are reputed to have a narrow genetic base, resulting from infrequent introduction of exotic germplasm into China. We have used several different molecular approaches to evaluate diversity and relatedness in a selection of 34 Chinese sorghums. The results indicated that different DNA marker technologies for germplasm assessment yield comparable results, but that a relatively new technique termed inter‐simple sequence repeat amplification (ISSR) was relatively rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
99
1
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 0 publications
13
99
1
12
Order By: Relevance
“…It was seven in silkworm (Pradeep et al, 2005), 10 in pistachio (Kebour et al, 2012), 12 in basmati (Nagaraju et al, 2002), 15 in lupine (Sbabou et al, 2010), 23 in Asparagus acutifolius (Sica et al, 2005), 30 in Lupinus spp. (Talhinhas et al, 2003) and 41 in sorghum (Yang et al, 1996). In our research, the most polymorphic bands was associated to (CA)n, (AC)n, and (AG)n primers.…”
Section: Discussionsupporting
confidence: 50%
“…It was seven in silkworm (Pradeep et al, 2005), 10 in pistachio (Kebour et al, 2012), 12 in basmati (Nagaraju et al, 2002), 15 in lupine (Sbabou et al, 2010), 23 in Asparagus acutifolius (Sica et al, 2005), 30 in Lupinus spp. (Talhinhas et al, 2003) and 41 in sorghum (Yang et al, 1996). In our research, the most polymorphic bands was associated to (CA)n, (AC)n, and (AG)n primers.…”
Section: Discussionsupporting
confidence: 50%
“…Comparison of the genetic distances generated by different molecular markers in diversity studies have been reported by several authors (Hahn et al, 1995;Russell et al, 1997;Yang et al, 1996) and have revealed only moderate agreement between genetic distance estimates made using RFLP and RAPD markers. Pejic et al (1998) compared different molecular markers to assess the genetic similarities between maize inbred lines and found great differences in the RAPD similarity clustering pattern.…”
Section: Discussionmentioning
confidence: 88%
“…Comparisons of different DNA markers for diversity studies in maize (Hahn et al, 1995;Smith et al, 1997;Ajmone Marsan et al, 1998;Pejic et al, 1998), barley (Russell et al, 1997), wheat (Bohn et al, 1999), cruciferous species (dos Santos et al, 1994;Thormann et al, 1994), potato (Mc Gregor et al, 2000), sorghum (Yang et al, 1996) and rice (Davierwala et al, 2000) have tried to evaluate the relative efficiencies of the different techniques available. However, in the case of maize, tropical and temperate populations differ from each other because tropical populations usually originate from composites with higher genetic variability and, most of the time, it is difficult to allocate tropical composites to well-defined heterotic groups by phenotypic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Sequences are amplified between two microsatellite loci (Wang et al, 1994;Wang et al, 2008;Zietkiewicz et al, 1994;Ratnaparkhe et al, 1998). Because of the higher annealing temperature and longer sequence of ISSR primers, they can yield more reliable and reproducible bands than random amplification of polymorphic DNA (RAPD; Nagaoka and Ogihara, 1997;Wolfe et al, 1998;Goulao et al, 2001;Qian et al, 2001), and the cost of these analyses is lower than that of some other markers such as restriction fragment length polymorphisms (RFLPs), simple sequence repeats (SSRs), and amplified fragment length polymorphisms (AFLPs; Yang et al, 1996;Wang et al, 2008). In addition to freedom from the necessity of obtaining genomic sequence information, ISSR markers are technically simpler than many other marker systems in the genetic diversity studies of plants (Ratnaparkhe et al, 1998;Bornet and Branchard, 2001;Ye et al, 2005).…”
Section: Introductionmentioning
confidence: 99%